Analisis Determinan Loyalitas Nasabah Bank Muamalat Indonesia - Syarifuddin Sulaiman (Jurnal Multidisiplin Madani, 2022)
This study aims to analyze the level of influence of service quality and satisfaction variables on customer loyalty. The target population is all customers who use deposit services. Determination of the number of samples using the Cochran formula, so the number of samples as many as 97 customers. Questionnaires were distributed to the respondents who had been targeted. The results showed that service quality and satisfaction partially or simultaneously affect customer loyalty. The analysis technique used is multiple linear regression analysis. The implication of this research is that service quality and satisfaction are empirically proven to have an impact on increasing customer loyalty.